Sites and Time of Oviposition of Euphyllura phillyreae Foerster on Olive Trees and on Phillyrea latifolia - Prophretou-Athanasiadou, D.A.; Tzanakakis, M.E (ENTOMOLOGIA HELLENICA, 1993)
The distribution of eggs of Euphyllura phillyreae Foerster (Homoptera: Aphalaridae) was recorded on twigs of olive trees and of Phillyrea latifolia L. in various locations of the Thessaloniki and Halkidiki prefectures of coastal northern Greece. On olive, the first eggs were observed in the last ten days of March and oviposition was intensified and became abundant only when the apical bud and the axillary leaf and flower buds started to swell. Eggs were laid mostly on swollen buds and on developing inflorescences. Oviposition preference was related to the stage of development of a bud and not to its location on the olive twig. On swollen leaf buds, most eggs were laid on the inner (upper) surface of the middle (second) pair of developing leaves, and fewer on the inner surface of the outer (first) pair and on the innermost (third) pair of leaves. On Phillyrea, eggs were deposited much earlier than on olive, on developing inflorescences. In choice and no-choice laboratory experiments, more eggs were laid on olive twigs bearing developing inflorescences, fewer eggs on twigs bearing only swollen terminal or axillary buds, and no eggs at all on twigs with only fully developed leaves of the previous year.